Palliative Care in Neurology - Voltz, Raymond; de Visser, Marianne; Oliver, David (Frontiers Media SA, 2020)
Over the last 50 years palliative care has usually been associated with cancer patients but more recently there has been increased discussion of the role of palliative care for neurological patients. In the past years, neurology has moved from being a purely diagnostic area to a very therapeutically active one. A further step needs to be taken to modify the therapeutic activity from "cure" to "care" depending on the patient's disease trajectory. Palliative care has been associated with care at the end of life, whereas it may be appropriate earlier in the disease progression, and will extend after death in the support of bereaved families. The care of patients with neurological disease, and their families, will encompass the psychological, spiritual and existential issues and neurologists, and the teams in which they work, should develop skills to consider all aspects of care, in order to maximize the quality of life of all involved, and enable patients to die peacefully.